Effect of chemical thinning on the fruit organoleptic parameters of ‘Majhoul’ date palm during the ripening stage - Mohamed ARBA; Atmane ELLADI; Hicham OUACHOUO (Acta Agriculturae Slovenica)
The aim of this research work was to study the effect of chemical thinning on the fruit organoleptic parameters of 'Majhoul' date palm during ripening. Trials were carried out in the Tinejdad region, Tafilalet area. Thinning treatments used are: (T0) treatment with tap water, NAA (Naphtalene acetic acid) treatments: (T1) 150 and 300 ppm 30 and 60 days after pollination and (T2) 250 and 500 ppm 30 and 60 days after pollination, and T3 manual thinning  used by the farmer. They are used on the fruits of three flowering phases. Obtained results showed that thinning treatments and flowering phases do not affect the titratable acidity of the fruit, while the two factors affect the pH of the fruit. The content of sugar in the fruit is higher in the control and manual treatments than in NAA treatments. It is also higher in the fruits of the early flowering than in those of the other phases. At the end of fruit development, the content of dry matter in the fruit increased for all the thinning treatments and flowering phases. The flowering phases and thinning treatments affect the rate of ripening, but there is no interaction between the two factors.